Pengaruh Resiko Perusahaan dan Ukuran Perusahaan terhadap Penghindaran Pajak - Febriani, Eri (Indonesian Accounting Literacy Journal, 2025)
This study aims to examine the effect of corporate risk and firm size on tax avoidance. The research uses secondary data from companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The sampling technique applied is purposive sampling. Data analysis is conducted using panel data regression with the Random Effect Model to test the influence of each variable on tax avoidance. The results indicate that corporate risk has a significant negative effect on tax avoidance, while firm size has a significant positive effect on tax avoidance.